From the Cover: Characterization of Isoniazid-Specific T-Cell Clones in Patients with anti-Tuberculosis Drug-Related Liver and Skin Injury. (1st November 2016) - Usui, Toru; Meng, Xiaoli; Saide, Katy; Farrell, John; Thomson, Paul; Whitaker, Paul; Watson, John; French, Neil S.; Kevin Park, B.; Naisbitt, Dean J.
Abstract : Isoniazid, rifampicin, pyrazinamide, and ethambutol are commonly used for the treatment of tuberculosis. Drug exposure is occasionally associated with liver and/or skin injury. The aim of this study was to determine whether drug-specific T-cells are detectable in patients with adverse reactions and if so characterize the nature of the T-cell response. Peripheral blood mononuclear cells (PBMC) from 6 patients with anti-tuberculosis drug-related adverse reactions (4 liver, 2 skin) were used to detect drug-responsive T-lymphocytes. Positive lymphocyte transformation test and/or ELIspot results were observed with all 6 patients. Over 3400 T-cell clones were generated from isoniazid, rifampicin, pyrazinamide, or ethambutol-treated PBMC. CD4+ clones from all 3 patients were activated to proliferate and secrete cytotoxic mediators (granzyme B, perforin, FasL) and effector (IFN-γ, Il-13) and regulatory (Il-10) cytokines with isoniazid, but not rifampicin, pyrazinamide, or ethambutol. Il-17 was not detected, while only 1 clone secreted Il-22. Isoniazid-responsive clones were not activated with other anti-tuberculosis drugs or isonicotinic acid albumin adducts. Activation of the clones with isoniazid was MHC class II-restricted and dependent on antigen-presenting cells. Most clones were activated rapidly even in the presence of the enzyme inhibitor 1-aminobenzotriazole. However, a time-dependent pathway of activation involving auto-oxidation of isoniazid was also observed. The discovery of isoniazid-specific CD4+ T-cell clones in patients with liver and skin injury suggests that the adaptive immune system is involved in the pathogenesis of both forms of iatrogenic disease.